Strategi Peningkatan Kinerja Keryawan Dengan Kompensasi Dan Lingkungan Kerja Melalui Kepuasan Kerja Sebagai Variable Intervening Pada PT. Rizky Anugrah Sejahtera - Huda, Khasbulloh; Sholeh, Rachmad; Eko Yuli Waluyo, Sugeng; Johan Efendi, Mohamad (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
This study aims to find out how the direct relationship between goals, work environment and job satisfaction on employee performance, and knowing the indirect relationship between goals, work environment and employee performance through job satisfaction at PT. Rizky Anugrah Sejahtera. The data collection method uses a questionnaire on 75 respondents who are all employees of PT. Rizky Anugrah Sejahtera with saturated sampling technique. Data processing was carried out using Smart PLS software version 3.0. The results show that the owner has a direct relationship to job satisfaction, the work environment has a direct relationship to job satisfaction, the owner has a direct relationship to employee performance, the work environment has a direct relationship to employee performance, job satisfaction has a direct relationship to performance employees, employees indirectly have a relationship to employee performance through job satisfaction and the work environment indirectly has a relationship to employee performance through job satisfaction.